kernel meal and its fermented product for growing ducks - I.A.K Bintang; A.P Sinurat; T Murtisari; T Pasaribu; T Purwadaria; T Haryati (Indonesian Center for Animal Research and Development (ICARD), 1999)
A series of experiment was carried out to evaluate the use of palm kernel meal and its fermented product in the ration of growing ducks. Treatments were arranged in a 2x3 factorial experiment, i.e. the combination between two processes (unfermented and fermented palm kernel meal) and three levels of ingredients in the diet (5, 10 and 15%). Four replicates were applied for each treatment, with 8 ducklings in each replicate. A control diet with no palm kernel meal was also formulated. All diets were formulated to have a similar protein and ME contents. Results of the experiment showed that fermentation process increased the nutrient composition (crude protein, true protein, phosphorus, and the metabolizable energy) and reduced its fibre and fat content. The feeding trial showed that neither the fermentation process, levels of ingredients nor the interactions of the two factors affected final body weight, feed consumption, feed conversion, carcass percentage and abdominal fat of the ducklings significantly. It is concluded that fermentation process improved the nutritional value of palm kernel meal and the inclusion of palm kernel meal (unfermented and fermented), up to 15% in the diet of ducks did not negatively affect the growthperformance and the carcass yield. Key words : Ducks, palm kernel meal, fermentation